2004
DOI: 10.1007/s00213-004-1804-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine and mecamylamine on cognition in rhesus monkeys

Abstract: Rationale-Nicotine and other agonists of nicotinic cholinergic receptors (nAChR) have been shown to improve performance in specific memory domains in rodents and monkeys. Such beneficial effects are observed in preclinical models of age-related cognitive decline, stimulating interest in nAChR ligands as possible therapeutics. Prior work has typically focused on assays of spatial working memory in rodent studies and visual recognition memory in monkey studies.Objective-The current study was conducted to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 95 publications
6
57
0
Order By: Relevance
“…The relatively minimal impact of raclopride and SCH23390 on response latencies in the memory procedures potentially contrasts with this conclusion. However, drug challenges may selectively slow sample versus choice latency in the vsPAL procedure in some cases (present raclopride study, Taffe et al 2002c), but not others (Katner et al 2004a), as well as selectively slow choice latency on 2-box over 4-box trials in the SOSS procedure (Taffe et al 2002a). In all cases the drugs significantly slowed BMS performance.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The relatively minimal impact of raclopride and SCH23390 on response latencies in the memory procedures potentially contrasts with this conclusion. However, drug challenges may selectively slow sample versus choice latency in the vsPAL procedure in some cases (present raclopride study, Taffe et al 2002c), but not others (Katner et al 2004a), as well as selectively slow choice latency on 2-box over 4-box trials in the SOSS procedure (Taffe et al 2002a). In all cases the drugs significantly slowed BMS performance.…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with this, a preliminary study suggested that aged monkeys may be particularly impaired on this task relative to young adult monkeys (Taffe et al 2003a). We have also shown that intact muscarinic and nicotinic cholinergic, as well as NMDA receptor glutamatergic, neurotransmission is critical for young adult monkeys to perform the task (Katner et al 2004a;Taffe et al 2002c). Here we show that normal D 2 -like, but not D 1 -like, dopaminergic neurotransmission is also required in nonhuman primates for object-location associative memory.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The monkeys were approximately 7-8 years of age (i.e., young adult) and weighed 8-12 kg at the beginning of the study. The monkeys had previously been trained on components of a behavioral test battery Taffe, 2004) and had participated in prior acute drug challenge studies with ketamine (Taffe et al, 2002b;Taffe et al, 2002c), scopolamine (Taffe et al, 2002c), nicotine and mecamylamine (Katner et al, 2004), and Δ 9 -tetrahydrocannabinol; these drugs were administered at least 3 months prior to the current study. The animals' diet was restricted 5 days per week to ensure consistent behavioral responding in the test battery while maintaining adequate growth rates.…”
Section: Animalsmentioning
confidence: 99%